2014
DOI: 10.1556/avet.2014.004
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic diversity of pigeon circovirus strains in Poland

Abstract: Pigeon circovirus (PiCV) is an immunosuppressive agent widespread throughout the world, which causes a disease in pigeons called Young Pigeon Disease Syndrome. The aim of the study was to evaluate the prevalence of PiCV in Poland and investigate the genetic diversity relative to other known PiCV isolates. Samples from 152 pigeon flocks (88 flocks of racing pigeons and 64 flocks of fancy pigeons) from various regions of Poland were tested by polymerase chain reaction and an approximately 326-base fragment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
(33 reference statements)
1
21
0
Order By: Relevance
“…The PiCV also targets other organs of the immune system, including the thymus and spleen (Woods et al 1993;Smyth & Caroll 1995;Coletti et al 2000;Soike et al 2001;Scullion & Scullion 2007). The virus or its genetic material have also been detected in the liver, kidneys, intestines, brain and skin (Smyth & Caroll 1995;Smyth et al 2001;Soike et al 2001;Ledwo n et al 2011;Stenzel & Pestka 2014;Dolka et al 2016). PiCV replicates in fast proliferating cells (epithelial cells) and immune system cells (lymphocytes and macrophages), and in this respect, it is similar to the psittacine circovirus (beak and feather disease virus, BFDV) .…”
Section: Clinical Pathology Of Picv Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PiCV also targets other organs of the immune system, including the thymus and spleen (Woods et al 1993;Smyth & Caroll 1995;Coletti et al 2000;Soike et al 2001;Scullion & Scullion 2007). The virus or its genetic material have also been detected in the liver, kidneys, intestines, brain and skin (Smyth & Caroll 1995;Smyth et al 2001;Soike et al 2001;Ledwo n et al 2011;Stenzel & Pestka 2014;Dolka et al 2016). PiCV replicates in fast proliferating cells (epithelial cells) and immune system cells (lymphocytes and macrophages), and in this respect, it is similar to the psittacine circovirus (beak and feather disease virus, BFDV) .…”
Section: Clinical Pathology Of Picv Infectionsmentioning
confidence: 99%
“…The prevalence of PiCV was determined by age and health status, and it was the highest (close to 100%) in young birds showing non-specific symptoms of the disease (Stenzel et al 2012). Asymptomatic infections were noted in 53% birds of all ages on average, and in 36% of adult domestic pigeons from breeding flocks (Stenzel & Pestka 2014;Stenzel et al 2014a;Stenzel et al 2016). Similar results were reported in studies of domestic pigeons conducted in Hungary (prevalence of less than 57%) and in China where PiCV DNA was isolated from 80.7% of diseased birds and 63.4% of asymptomatic birds (Zhang et al 2011;Cs agola et al 2012).…”
Section: Epidemiology Of Picv Infectionsmentioning
confidence: 99%
“…It has been shown that, despite the antigenic differences between LaSota and PPMV-1 strains, this vaccine effectively protects against disease caused by PPMV-1 (Marlier and Vindevogel 2006). However, an increasing number of breaking post-vaccination immunity cases may be associated with immunosuppression caused by very prevalent PiCV infection (Stenzel et al 2012, Stenzel andPestka 2014). The immunoprophylaxis of paramyxovirosis in pigeons does not involve live vaccines, because they are less immunogenic, and in the case of carrier pigeons the spread of vaccine virus may occur in areas where vaccinations against the ND virus are not applied (Śmietanka and Minta 2011a).…”
Section: Disease Controlmentioning
confidence: 99%
“…The role of PiCV and PPMV-1 in this process has not been sufficiently explained. According to the recent reports, the evolution of PPMV-1, genetic diversity of PiCV, and possibility of recombination can lead to the creation of emerging viral variants with new properties (19,20,22). More research on their pathogenesis is needed to determine if feather abnormalities have resulted from direct or indirect effects of infections, intoxications, liver dysfunctions or other factors.…”
Section: Resultsmentioning
confidence: 99%